2017
DOI: 10.1051/e3sconf/20171902019
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of heavy metals from cementitious composites made of new ternary cements

Abstract: Abstract. The paper presents a comparison of research methods concerning the leaching of harmful substances (selected heavy metal cations ie. Pb, Cu, Zn and Cr) and their degree of immobilization in cement matrices. The new types of ternary cements were used in the study, where a large proportion of cement clinker was replaced by other non-clinker components -industrial wastes, ie. siliceous fly ash from power industry and granulated blast furnace slag from the iron and steel industry. In studied cementitious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The slightly higher level of leaching of metal ions, i.e., Cu, Pb, Cr, Ba (but also below the level permitted by law) was observed for concrete produced with the addition of fly ash from biomass burning [5]. Also, the research by Kuterasi ńska-Warwas and Król [69] confirms that cement composite matrices immobilize heavy metal ions well. The authors showed that the new cement CEM II/C and CEM VI composite cement containing the addition of industrial waste are suitable for the use of matrices for the immobilization of heavy metals (Cu, Zn, Cr and Pb).…”
Section: Leaching Of Metal Ions From Mortars Modified With Wastementioning
confidence: 72%
“…The slightly higher level of leaching of metal ions, i.e., Cu, Pb, Cr, Ba (but also below the level permitted by law) was observed for concrete produced with the addition of fly ash from biomass burning [5]. Also, the research by Kuterasi ńska-Warwas and Król [69] confirms that cement composite matrices immobilize heavy metal ions well. The authors showed that the new cement CEM II/C and CEM VI composite cement containing the addition of industrial waste are suitable for the use of matrices for the immobilization of heavy metals (Cu, Zn, Cr and Pb).…”
Section: Leaching Of Metal Ions From Mortars Modified With Wastementioning
confidence: 72%